Genomic insights into genetic diversity and seed coat color change in common bean composite populations - Plestenjak, Eva; Neji, Mohamed; Sinkovič, Lovro; Meglič, Vladimir; Pipan, Barbara (Frontiers in Plant Science, 2025)
IntroductionThe color of the seed coat of common bean (Phaseolus vulgaris L.) is an important trait influencing marketability and consumer preferences. An understanding of the genetic mechanisms underlying seed coat color variation can aid in breeding programs aimed at improving esthetic and agronomic traits. This study investigates the genetic diversity and molecular mechanisms associated with seed coat color change in composite bean populations through phenotypic analysis and whole genome sequencing (WGS).MethodsFour composite populations and two standard varieties of common bean were cultivated over a two-year period and seed coat color and morphological traits were assessed. WGS was performed on 19 phenotypes and yielded 427 GB of data with an average sequencing depth of 30×. More than 8.6 million high-confidence single nucleotide polymorphisms (SNPs) were identified. Genetic diversity metrics such as nucleotide diversity (π), observed heterozygosity (Ho), expected heterozygosity (He) and allelic richness (Ar) were calculated. Population structure was analyzed using Fst, principal component analysis (PCA) and clustering. Cross-population statistics (XP-CLR and XP-EHH) were used to identify selection signals associated with seed coat color change. Gene Ontology (GO) and KEGG enrichment analyzes were performed for candidate genomic regions.ResultsPhenotypic analysis revealed significant differences in seed coat color among the four composite populations, with notable changes among years. The populations exhibited different growth habits and plant types, especially KIS_Amand and SRGB_00366, which showed the highest phenotypic diversity in seed coat color. WGS identified 8.6 million SNPs, with chromosomes 4 and 1 having the highest SNP density (11% each), while chromosomes 3 and 6 had the lowest. KIS_Amand had the highest genetic diversity (π = 0.222, Ar = 1.380) and SRGB_00189 the lowest (π = 0.067, Ar = 1.327). SRGB_00366 showed moderate genetic diversity (π = 0.173, Ar = 1.338) and INCBN_03048 showed medium diversity (π = 0.124, Ar = 1.047). The Fst values indicated a strong genetic differentiation, especially between the two standard varieties ETNA and Golden_Gate (Fst = 0.704) and the composite populations. Selective sweep analysis with XP-CLR and XP-EHH identified 118 significant regions associated with seed coat color change, with most regions located on chromosomes 4, 9, 10 and 11. Phosphatidylinositol signaling pathways were highly enriched in candidate regions, indicating that cellular transport mechanisms play a critical role in seed coat pigmentation. Key GO terms included phosphatidylinositol-biphosphate binding, exocytosis, and vesicle-mediated transport, suggesting a link between cellular transport and pigment deposition in the seed coat.DiscussionThe study demonstrates significant genetic diversity within and among common bean composite populations, with KIS_Amand and SRGB_00366 exhibiting the highest phenotypic and genetic variability. The identification of selective sweeps and the enrichment of phosphatidylinositol-related pathways provide new insights into the molecular mechanisms controlling seed coat color variation. The strong genetic differentiation between standard varieties and composite populations highlights the role of selective breeding in shaping the genetic landscape of common bean. The results suggest that variation in seed coat color is controlled by both regulatory and structural genetic changes, providing valuable information for breeding programs.ConclusionThis study provides a detailed analysis of the genetic architecture of seed coat color variation in common bean. The identification of key genomic regions and pathways associated with seed pigmentation improves our understanding of the complex genetic interactions underlying this trait. These results provide valuable genomic resources for future breeding efforts aimed at improving seed color and other important traits in common bean.